2015
DOI: 10.1097/sap.0000000000000365
|View full text |Cite
|
Sign up to set email alerts
|

The Scope of Practice of Hand Surgery Within Plastic Surgery

Abstract: In many residency programs, hand surgery exposure is in the setting of trauma and emergencies. The inclusion of complex elective hand surgeries within a plastic surgery practice and residency program allows residents to see the full spectrum of hand surgery. This allows them to make an informed decision regarding whether to seek subspecialty training and continue the participation of plastic surgeons in the full spectrum of hand surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…In a 2015 survey study, nearly half of hand surgeons managed vascular and infectious conditions of the elbow and above, and 86% of surgeons treated soft tissue injuries of the upper arm. 28 In addition, a national survey study among arthroscopists found that three and nine times as many sports surgeons operated on the elbow and shoulder, respectively, compared with those who operated on the wrist. 29…”
Section: Discussionmentioning
confidence: 99%
“…In a 2015 survey study, nearly half of hand surgeons managed vascular and infectious conditions of the elbow and above, and 86% of surgeons treated soft tissue injuries of the upper arm. 28 In addition, a national survey study among arthroscopists found that three and nine times as many sports surgeons operated on the elbow and shoulder, respectively, compared with those who operated on the wrist. 29…”
Section: Discussionmentioning
confidence: 99%
“…Entgegen der Wahrnehmung der Plastischen Chirurgie in der breiten Öffentlichkeit übernehmen plastisch-chirurgische Abteilungen an öffentlichen Spitälern als Letztversorger einen maßgeblichen Anteil in der Krankenversorgung, wobei der Schwerpunkt im plastisch-rekonstruktiven Behandlungsspektrum liegt [5][6][7][8]. Dazu zählen unter anderem die Versorgung komplexer Handverletzungen inklusive Replantationen, die Behandlung Schwerbrandverletzter, die chirurgische Therapie akuter Weichteil-und Knocheninfektionen sowie die interdisziplinäre Tumorchirurgie [9] -insbesondere im Falle der untersuchten universitären Abteilung in Graz mit überregionalem Versorgungsauftrag und einem dadurch entstehenden Einzugsgebiet mit über 2 000 000 Einwohnern.…”
Section: Resultsunclassified
“…This is consistent with previous findings demonstrating that, among surveyed plastic surgeons, softtissue injuries were the primary issue addressed while taking hand call. 4 Silvestre et al surveyed hand fellows in Accreditation Council for Graduate Medical Education (ACGME) approved programs and found that plastic surgery hand fellows reported greater numbers of soft-tissue cases, for example, wound closures with grafts and flaps, as well as microvascular cases, while orthopaedic hand fellows reported a greater number of bone and joint procedures, including those involving fracture and dislocation management. 7 In our analysis, only 22.7% of procedures involved only bone and/or joint.…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 survey by the American Council of Academic Plastic Surgeons (ACAPS) found that half of the respondents reported taking hand call, with 78% reporting that all plastic surgery faculty at their academic institution take hand call, regardless of whether or not they have subspecialty hand training. 4 Another 2013 survey of plastic surgery residency PDs identified nine essential hand surgeries that residents were expected to master prior to graduation, indicating a baseline level of hand surgery proficiency among all plastic surgery residency graduates. 5 Although previous studies have sought to delineate the practice of plastic surgery-trained hand surgeons, no known studies analyze the trends in hand surgeries performed by all plastic surgeons, regardless of fellowship training or SOTH status.…”
Section: Introductionmentioning
confidence: 99%